DETERMINANTS OF MUZAKKI'S INTEREST IN PAYING ZAKAT TO BAZNAS AT SOLOK CITY - Lili Wahyuni; Juita Sukraini; Hevi Novita (Jurnal Ekonomi, 2023)
The incompatibility of the realization of zakat funds received by BAZNAS in Solok City with the existing potential zakat income is a phenomenon that is currently occurring in Solok City. This research aims to determine the influence of: (1) The quality of accounting information on Muzakki's interest in paying zakat to BAZNAS Solok City; (2) Transparency of financial reporting regarding Muzakki's interest in paying Zakat to BAZNAS Solok City; and (3) Quality of Accounting Information and Transparency of Financial Reports regarding Muzakki's interest in paying Zakat to BAZNAS Solok City. This research used quantitative research and used a causal-comparative approach. All Muzakki registered with BAZNAS Solok City are the population in this study, where in sampling a simple random sampling technique was used where the sample size was determined using the Slovin formula. This research data was obtained by distributing questionnaires directly to respondents. Partially, the quality of accounting information and transparency of financial reporting have a significant effect on Muzakki's interest in paying zakat. Simultaneously, the quality of accounting information and transparency of financial reporting influence Muzakki's interest in paying zakat. As many as 58.8% of Muzakki's interest in paying zakat to BAZNAS Solok City is influenced by the quality of accounting information and transparency of financial reporting, while 41.2% is influenced by other variables outside of the variables in this research.